Occurrence of extended-spectrum β-lactamase, AmpC, and carbapenemase-producing genes in gram-negative bacterial isolates from human immunodeficiency virus infected patients. Issue 12 (December 2021) - Rameshkumar, Marimuthu Ragavan; Arunagirinathan, Narasingam; Senthamilselvan, Balasubramanian; Swathirajan, Chinnambedu Ravichandran; Solomon, Sunil Suhas; Vignesh, Ramachandran; Balakrishnan, Pachamuthu; Aljowaie, Reem M.; Almaary, Khalid S.; Chen, Tse-Wei
Abstract: Background: Progressive decline of immune response in HIV patients makes them susceptible to frequent bacterial infections. High usage of antibiotics influences the emergence of multidrug-resistant bacteria and worsens the clinical outcomes. In this study, the occurrence of drug-resistant genes in Gram-negative bacterial isolates from HIV patients in South India was analyzed. Methods: A total of 173 Gram-negative bacterial (GNB) isolates from HIV patients were screened for antibiotic susceptibility profile using the Kirby-Bauer diskdiffusion method. Positivity of drug-resistant genes was analyzed using polymerase chain reaction method. Results: In this study, 72.8% of bacterial isolates were obtained from urine specimens, and Escherichia coli (47.4%) was the predominantly isolated bacterium. Overall, 87.3% and 83.2% of GNB were resistant to 3rd generation cephalosporin antibiotics such as cefotaxime and ceftazidime, respectively, 56.6% were resistant to cephamycin (cefoxitin) and 43% to carbapenem (imipenem) antibiotics. Extended-spectrum β-lactamases (ESBL) production was noted among 79.5% of GNB isolates, followed by AmpC (57.1%) and Metallo β-lactamases (37.3%). Molecular analysis revealed that ESBL genes such as bla TEM (94.1%), bla CTX-M (89.2%), and bla SHV (24.2%) were detected at higher levels among GNB isolates. Carbapenemase-producing genes such as bla OXA-48 (20%), bla OXA-23 (2.6%), and both bla OXA-23 and bla OXA-51 like genes (2.6%) and AmpC producing genes such as bla CIT (26.7%), bla DHA (3.6%), and bla ACC (1.8%) were detected at low-level. Conclusions: This study concludes that ESBL producing genes are detected at high level among gram-negative bacterial isolates from HIV patients in South India.